2018
DOI: 10.3390/met8110899
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Galvanic Corrosion of Steam Generator Materials within Pores of Magnetite Flakes in Alkaline Solutions

Abstract: In secondary coolant system of the pressurized water reactors, the reduced corrosion products such as metallic Cu and Pb particles were accumulated in the pores of the magnetite flakes and electrically contacted to the steam generator materials. The micro-galvanic corrosion behavior of steam generator materials (steam generator tube materials: Alloy 600 and Alloy 690, steam generator tube sheet materials: SA508 Gr.3) contacted to the corrosion products (magnetite, Cu, and Pb) was investigated in an alkaline so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Many researchers have presented that aggressive chemical impurities are concentrated within the micro-pores of the SG tube deposits and tube sheet sludge owing to the evaporation of secondary water within the micro-pores [22,23]. These phenomena accelerated the corrosion rate of the SG components owing to the formation of severe corrosive environments [22,23]. Hence, the SG tube deposit specimens, which concentrated the chemical impurities, could be widely used in many investigations related to the corrosion behaviors.…”
Section: Simulation Of Chemical Impurity Concentration Within the Micmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have presented that aggressive chemical impurities are concentrated within the micro-pores of the SG tube deposits and tube sheet sludge owing to the evaporation of secondary water within the micro-pores [22,23]. These phenomena accelerated the corrosion rate of the SG components owing to the formation of severe corrosive environments [22,23]. Hence, the SG tube deposit specimens, which concentrated the chemical impurities, could be widely used in many investigations related to the corrosion behaviors.…”
Section: Simulation Of Chemical Impurity Concentration Within the Micmentioning
confidence: 99%
“…In the secondary side of the PWR, magnetite is mainly composed of SG tube deposits. However, the trace amount of other phases such as trevorite (Ni 2 FeO 4 ), jacobsite (Mn 2 FeO 4 ), chromite (FeCr 2 O 4 ), and metallic Cu and Pb particles may also constitute the SG tube deposits [22,23]. Recently, Electricité de France simulated the SG tube fouling using the experimental loop called FORTRAND [24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small flow channel size, PCHEs are expected to be much more vulnerable to fouling compared to conventional SGs. Moreover, some studies have reported that corrosion of the SG tube materials is accelerated by the concentration of aggressive chemical impurities within the pores of the fouling layer [16][17][18][19]. Classic shell-and-tube SG tubing in PWRs can be damaged by a variety of degradation modes, including stress corrosion cracking, intergranular attack, pitting, and fretting-wear [11][12][13][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite deposits accumulated in SGs can deteriorate the performance and integrity of the SG [6][7][8][9][10][11][12][13]. The porous deposits have a lower thermal conductivity than the SG tubing [6][7][8]; therefore, the heat transfer capability of the SG tubing decreases, and the temperature of the SG tube wall increases.…”
Section: Introductionmentioning
confidence: 99%